2004
DOI: 10.1152/ajpregu.00412.2003
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhage-induced acute lung injury is TLR-4 dependent

Abstract: Toll-like receptor 4 (TLR-4), initially identified as an LPS receptor, is critical to the signaling of a variety of danger signals, including heat shock protein 60, fibrinogen, and fibronectin. Recent data also suggest that TLR-4 plays a role in determining survival in both endotoxemia and hemorrhagic shock. We hypothesized that a functional TLR-4 would be required for hemorrhage and endotoxin-induced acute lung injury. Hemorrhage- and endotoxin-induced lung TNF-alpha mRNA and protein production, neutrophil ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
91
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(94 citation statements)
references
References 52 publications
1
91
0
2
Order By: Relevance
“…Previous studies suggested that TLR4 participates in the pathogenesis of non-infectious lung injury. TLR4 recognizes diesel exhaust particles (Inoue et al, 2006) and pollutant ozone (Kleeberger et al, 2010), expressed in smoke-induced lung injury (Karimi et al, 2006), and is required for hemorrhage-induced lung tumor necrosis factor-α production, neutrophil accumulation, and protein permeability (Barsness et al, 2004), supporting that TLR4 accelerates the progress of non-infectious lung disease. However, TLR4 maintained appropriate levels of anti-apoptotic responses during oxidant stress, and thus played a protective role in oxidant-mediated lung injury (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that TLR4 participates in the pathogenesis of non-infectious lung injury. TLR4 recognizes diesel exhaust particles (Inoue et al, 2006) and pollutant ozone (Kleeberger et al, 2010), expressed in smoke-induced lung injury (Karimi et al, 2006), and is required for hemorrhage-induced lung tumor necrosis factor-α production, neutrophil accumulation, and protein permeability (Barsness et al, 2004), supporting that TLR4 accelerates the progress of non-infectious lung disease. However, TLR4 maintained appropriate levels of anti-apoptotic responses during oxidant stress, and thus played a protective role in oxidant-mediated lung injury (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…by ischemia-reperfusion (29) or in hemorrhage-induced acute lung injury (30)). However, efficient inhibitors of TLR4 activation in inflammatory conditions are not yet in therapeutic use, although several of them are at the advanced stages of clinical trials (31).…”
Section: Discussionmentioning
confidence: 99%
“…(iii) In tissue injury and repair, several recent studies examined the expression patterns of TLR2 and/or TLR4 in smoke-induced lung injury and in patients with chronic obstructive pulmonary disease [63][64][65]. Hemorrhage-induced lung TNF-a production, neutrophil accumulation, and protein permeability, but not NF-kB activation, were dependent on a functional TLR4 [66]. TLR4-TLR2 cross-talk activated a positive-feedback signal leading to alveolar macrophage priming and exaggerated lung inflammation in response to invading pathogens during hemorrhage-induced acute lung injury [67].…”
Section: Toll-like Receptorsmentioning
confidence: 99%